“Pin Method” for Endoscopic Lumbar Interbody Fusion - Huang, Ting-Chun (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Endoscopic lumbar interbody fusion using a cage can have a similar fusion rate as minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) or open lumbar interbody fusion. Direct visual control during cage insertion is the key to prevent neural structure incarceration in endoscopic lumbar interbody fusion. Creating a track with any kind of retractor or cannula for cage insertion under fluoroscopic guidance is not safe enough, because the retractor and cannula can create many blind spots and can displace during cage insertion.Method The pin method utilizes two flexible metallic guide pins inserted from the skin incision through the annulotomy site into the disk space until the anterior longitudinal ligament is reached under direct endoscopic monitoring. The two guide pins could be oriented parallel or perpendicular or even reduce to one or increase to many as needed to serve as a sliding track and a see-through barrier to prevent neural incarceration.Results and Conclusion Two cases of L4/L5 grade 2 spondylolisthesis with neurogenic claudication were treated with endoscopic lumbar interbody fusion with 1-year follow-up, and the visual analog scale (VAS) score, Oswestry Disability Index (ODI) score, EuroQol five-dimensional questionnaire (EQ-5D, %) score, and modified Macnab score all improved greatly in both. The author developed an original, cheap, accessible, and safe method called the “pin method,” which can be used in both full-endoscopic and biportal surgery and can apply to various approaches and has no limitation on the size and shape of the cage.
Keywords: endoscopy; interbody fusion; lumbar; transforaminal; biportal